Financial literacy in South African healthcare professionals: An unmet need in health professions education - Millen, A.; Stacey, A. (South African Journal of Higher Education, 2021)
The holistic training of healthcare professionals as a strategy to build the healthcare system has received considerable attention. As part of training a holistic workforce, it is expected the healthcare professionals be component in management and governance. Financial literacy is low globally and impacts financial decision-making and business management. Despite high levels of education, medical professionals elsewhere in the world have low financial literacy. Financial literacy levels in South African healthcare professionals are unknown. This study investigated the degree of and contributors to financial literacy in South African healthcare professionals. A validated financial literacy questionnaire was completed by 473 healthcare professionals, of whom 130 owned private practices. Financial literacy scores were determined as a composite score based on financial knowledge, financial behaviour and financial attitudes. The independent contribution of demographic factors to financial literacy were determined in multivariate linear regression analysis. Financial literacy in healthcare professionals was relatively high (73%). Of the total cohort 24%, 27% and 63% did not reach acceptable scores for financial knowledge, behaviour, and attitudes, respectively. Sex, medical specialty and being in private healthcare predicted financial knowledge scores. Higher income and self-rated financial knowledge were associated with financial literacy. In business owners, business-specific financial literacy was low (51%), and not associated with general financial literacy (r=-0.11, p=0.40). Education in economics and finance predicted business-related financial literacy scores (p=0.02). Financial attitudes that favour the short term may impact financial decision-making in healthcare professionals in managing small businesses and state healthcare facilities. Current approaches in health professions education may impact the success of the healthcare system in South Africa.